MITI and the Japanese miracle : the growth of industrial policy, 1925-1975 - Johnson, Chalmers, 1931-2010 (Stanford University Press, 1982)
Annotation Positioning Statement: An explosive account of the resentments American policies are sowing around the world and of the payback that will be our harvest in the twenty-first century The hardcover received great review and media coverage. The author is incredibly well-connected and in constant demand as a speaker. The perfect match of author and subject.
Keywords: Japan. -- Tsūshō Sangyōshō -- History.; Japon. -- Tsūshō Sangyōshō -- Histoire.; Japan. -- Tsūshō Sangyōshō; Japan -- Ministry of International Trade and Industry; Chōsen Kōgei Kenkyūkai; Japan -- Ministry of International Trade and Industry.; Industrial policy -- Japan -- History.; Electronic books.; Politique industrielle -- Japon -- Histoire.; Livres numériques.; e-books.; POLITICAL SCIENCE -- Public Affairs & Administration.; Politique industrielle.; Histoire économique.; Japon.; Industrial policy; Japan; Industriepolitik; Industrie; Wachstum; Außenhandelspolitik; Industriepolitiek.; Ministeries.; Politique industrielle -- Japon.; Japon -- Politique économique -- 1918-1945.; Japon -- Politique économique -- 1945-1989.; History